Specific rehabilitation exercise for the treatment of patients with chronic low back pain - Tomanova, Michaela; Lippert-Grüner, Marcela; Lhotska, Lenka (Journal of physical therapy science, 2015)
[Purpose] To evaluate the efficacy of our special rehabilitation method for patients with low back pain (LBP). [Subjects and Methods] All participants (n=33) received at least five individual 30-minute therapy sessions per week using the INFINITY method(®) and six group therapy sessions per week in a gymnasium and swimming pool, each lasting 30 minutes and including the INFINITY method(®). The treatment lasted between four to seven weeks. Plantar function using a graphic method (computer plantography), graphical quantification of postural control during static standing (posturography), and pain were measured and evaluated before and after rehabilitation therapy. The INFINITY method(®) is a special rehabilitation method for patients with musculoskeletal problems. The method focuses on stabilization and strengthening of the trunk, dorsal and abdominal muscles, including the deep stabilization system which is closely linked with diaphragmatic breathing. It teaches the central nervous system to control muscles more precisely. [Results] Plantar functions, postural control in the upright stance and pain of LBP patients were significantly improved by 4-7 weeks of rehabilitation treatment with the INFINITY method(®). There were significant differences in all measured dependent variables of the patients between before and after treatment. [Conclusion] Rehabilitation therapy with the INFINITY method(®) positively influences body stabilization and pain in patients with problems of the lumbar spine. This method presents a new improved approach (with enhanced effect) to rehabilitation therapy for LBP patients.